A detailed paleomagnetic and rock-magnetic investigation of the Matuyama-Brunhes geomagnetic reversal recorded in the tephra-paleosol sequence of Tlaxcala (Central Mexico) - Soler-Arechalde, Ana M.; Goguitchaichvili, Avto; Carrancho, Ángel; Sedov, Sergey; Caballero-Miranda, Cecilia I.; Ortega, Beatriz; Solis, Berenice; Contreras, Juan J. Morales; Urrutia-Fucugauchi, Jaime; Bautista, Francisco (Frontiers in Earth Science, 2015)
Geomagnetic reversals are global phenomena, for about 50 years the paleomagnetists attempted to acquire as many detailed records as possible using the magnetic memory of sediments and lava flows. Yet, transitional field behavior remains poorly characterized largely because of sporadic aspect of volcanic eruptions. In some specific cases, paleosols such as those developed from alluvial or aeolian sediments, may also record the variations of the Geomagnetic Field across the polarity changes. Here, we report a detailed paleomagnetic and rock-magnetic investigation on some radiometrically dated chromic luvisols located in Central Mexico carrying detrital or chemical remanent magnetization. The research was developed in order i) to demonstrate the primary origin of the magnetic remanence and ii) to show that paleosoils are good candidates to provide a high resolution record of the behavior of geomagnetic field during reversals. The lower part of the paleosoil sequence shows a clearly defined reverse polarity magnetization followed by geomagnetically unstable transitional field and ended by normal polarity remanence. Our AMS and rock magnetic data suggest that magnetization is acquired during the initial stage of soil formation in context of active volcanic activity since magnetic fabric is essentially sedimentary and reverse and normal polarity paleodirections are almost antipodal. Titanomagnetites are identified as main magnetic carriers of rock-magnetic measurements including thermomagnetics and hysteresis cycles. We propose that the transition recorded in this study correspond to the B-M boundary, considering the K-Ar datings available at the sequence bottom and that the chromic luvisols are potentially good recorders of the paleosecular variation. The identification of the B-M boundary within the studied sequence has fundamental significance for improving the chronological scale of Tlaxcala paleosol-sedimentary sequence and its correlation with the global proxies.